Effect of the activity of Boswellia Carterii extracts on preservation of ground meat (Journal of the College of Education for Women, 2019)
The study aimed to know the effect of the use alcoholic ethanol extraction of Boswellia Carterii In prolonging the period of preservation cooled ground meat in 4C for 6 days, it has been mixing ground meat with 150,300,450 mg/ml of alcoholic extract Consecutive, Where (0 was the control sample), All samples were stored separately for 0 , 3 , 6 days in Refrigerator temperature 4 C, Conducted by some microbial tests, Results have shown that mixing the ground meat with Boswellia Carterii extraction Led to prolong the storage of meat for 6 days at 4 C .and the Best result came when adding alcoholic ethanol extract of Boswellia Carterii by 450mg/ml Which Equal 0.9 g ,that reducing microbial load more higher than 150&300 mg/ml. All of these samples conformed to the Iraqi standard in terms of human consumption.